Konfigurasi dan Implementasi Enterprise Resource Planning Modul CRM(Customer Relationship Management) dengan ODOO Studi Kasus Kopi Sagaleh - Yosephine Leonie; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
Kopi Sagaleh has a weakness, namely it does not have a CRM(Customer Relationship Management) module. the purpose of the research is the configuration and implementation of the CRM(Customer Relationship Management) module with Odoo. the method used in the study is the ASAP method. the expected results in this study are the implementation of the CRM module with Odoo with 5 menus: customer, my pipeline, pipeline analysis, activity types, and tags.